Selected Issues in the Development of Tourism in Kraków in the 21st Century - Kurek, Włodzimierz; Faracik, Robert (Turyzm/Tourism, 2008)
The tourism industry in Poland has experienced dramatic development at the beginning of the 21st c. Large cities have seen in-depth changes, both spatial and functional, from the impact of tourism. As one of Poland's most popular tourism centres, Kraków is undergoing a process of intensive tourism development. This traditional centre of domestic sightseeing is now changing into a multifunctional International tourist centre.